Group work: a powerful site of resistance for migrant women experiencing gender-based violence. (14th July 2017) - Sharma, Sandhya; Marsh, Vicky
Abstract : During 2016, Safety4Sisters North West, a small women's organisation based in Manchester, UK, worked with 61 women who had insecure immigration status and had experienced gender-based violence. This article examines the themes that arose from the project's group work highlighting the realities of vulnerable migrant women living at society's margins, resisting and navigating both patriarchal and immigration control within the context of austerity.